Bobot Saluran Pencernaan Ayam Kampung yang diberi Tepung Tongkol Jagung Fermentasi EM4 Sebagai Pengganti Dedak Dalam Ransum: Digestive Tract Weight of Kampung Chickens Fed Diets Containing EM4-Fermented Corn Cob Flour as a Rice Bran Replacement - Nelwida, Nelwida; Fitri, Siska Mutia; Nurhayati, Nurhayati; Depison, Depison; Handoko, Heru; Sumadja, Wiwaha Anas (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Kampung chickens are an important source of animal protein in Indonesia, but the quality of local feed such as rice bran is often low in protein and high in crude fiber. Corn cobs as an alternative also have high fiber limitations, so they need to be fermented with EM4 to increase their nutritional value. Objective: This study aims to determine the digestive tract weight of native chickens fed EM4-fermented corn cobs as a substitute for rice bran in their diet. Purpose: This study aims to determine the digestive tract weight of native chickens fed EM4-fermented corn cobs as a substitute for rice bran in their diet.  Methods: This study used 200 DOC ULU kampung chickens. The experimental diets had the same basal composition but differed in the proportions of rice bran and fermented corn cob flour: P0 (16% rice bran, 0% TJF), P1 (12% rice bran, 4% TJF), P2 (8% rice bran, 8% TJF), P3 (4% rice bran, 12% TJF), and P4 (0% rice bran, 16% TJF). A completely randomized design (CRD) with five treatments and four replications was applied with each experimental unit using 10 chickens. Observation parameters included feed consumption, slaughter weight, relative weight of the ventricle, relative weight and length of the small intestine taken from two chickens per treatment unit. Data were analyzed statistically using analysis of variance (ANOVA). The effect of treatment on the tested parameters was analyzed using Duncan's Multiple Range Test to determine differences between treatments. Results: The results of the study showed that the provision of fermented corn cob flour EM4 as a substitute for rice bran in the ration up to 16% had no significant effect (P>0.05) on ration consumption, slaughter weight, relative weight and length of the small intestine, but significantly (P<0.05) increased the weight of the ventricle. Conclusion: It was concluded that the provision of fermented corn cob flour with EM4 could replace rice bran up to 16% in the ration without disrupting the performance of the digestive tract except for the performance of the ventricle in native chickens.